Analisis Tingkat Kepuasan Kerja Karyawan di LP3I Group Dengan Menggunakan Metode Human Resources Index (HR Index) Survey - Kaban, Karya Bakti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research was conducted on LP3I Group employees with the aim of measuring the level of employee job satisfaction. Research and analysis is carried out through surveys of employees which are carried out periodically and which are measured using the same questions so that progress can be seen from the programs that have been carried out. The purpose of measurement is also to build a positive, active and collaborative work environment. LP3I Group employees themselves consist of employees at the LP3I Foundation, employees at the Private Higher Education Group or PTS which consists of the LP3I Jakarta Polytechnic (PLJ) along with the expansion campus and PTS Development Accounting Academy (AKMA) Bengkulu, and employees at the College Branch Group (Education Non-Formal) with around 19 branches throughout Indonesia. In this employee satisfaction survey, the Human Resources Index (HR Index) concept proposed by Fredrick E. Schuster in the book Human Resources Management; Concepts, Cases and Reading, in 1985. The method used in this research is descriptive qualitative method. Data analysis was carried out through simple linear regression. The research instrument used was a questionnaire which was calculated in data tabulation. The results of the employee satisfaction survey are then compared with present norms, namely the average survey value of employee satisfaction in various companies in the world based on the HR Index survey. The results of the research show that employee satisfaction in the LP3I Group on average is 3.62 (from a maximum of 5) which is higher than the standard or present norms value which is 3.38, but in total the LP3I Group HR Index value has decreased slightly. when compared with the results of the HR Index employee satisfaction survey in 2021 with the number 3.69 and in 2022 with the number 3.68.